Tourism and National–Ethnic Identities: A Bibliometric Analysis - Fatemeh Shekari (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2022)
Tourism can both strengthen and undermine national–ethnic identities on the one hand, but on the other hand it can lead to their gradual disappearance. National–ethnic identities also pose a challenge to the rapid homogenization of cultures caused by globalization. In spite of more than five decades of research on tourism and national–ethnic identity, there is a research gap given the lack of a comprehensive review of the literature. In this respect, the present study aimed to conduct a quantitative literature review using bibliometric analysis. In order to understand the social and conceptual structure of the research field, the study used VOSviewer_1.6.18 software to carry out performance analysis and science mapping of 383 documents indexed in the Scopus database. The findings indicate that in the last decade, heritage tourism (particularly among diaspora and immigrants), the representation of outbound tourists’ national–ethnic identity, and the representation of destinations’ national–ethnic identity through tourism were among the most popular research topics worthy of further consideration in future studies. Introduction Tourism can leave dual effects on national –ethnic identities. Not only can it strengthen the collective national–ethnic identities, but also  as one of the drivers of cultural globalization, it can accelerate the disappearance of such identities. In addition, national–ethnic identity poses an obstacle to the rapid cultural homogenization caused by globalization. In spite of more than five decades of research on tourism and national–ethnic identity, there is a research gap given the lack of a comprehensive and systematic review of the literature. To address this gap, the present study aimed to conduct a quantitative literature review using bibliometric analysis. Materials and MethodsThe statistical population of the study consisted of documents in the field of national–ethnic identity and tourism that were indexed in the Scopus database. A systematic search in the Scopus database on December 23, 2021, resulted in 338 records, including journal articles, book chapters, and conference papers with national identity or ethnic identity and tourism in their title, abstract, or keywords. Performance analysis and science mapping using VOSviewer_1.6.18 software were conducted in order to identify the most influential documents, authors, sources, institutions, and countries, and also to understand the social and conceptual structure of the research field. Results and DiscussionThe results showed that research on national–ethnic identity and tourism has significantly increased since 1976, with the most of articles published in 2021. The most influential documents, in order of their normalized citations, were‏ Packer et al. (2019), Park (2010), Wang et al. (2021), and Zhang et al. (2018). The US, the UK, and Australia had the highest number of documents and citations. The most influential authors, in order of their normalized citations, were morais d.b., smith a., bhandari k., and palmer c. Performance analysis also revealed the most influential sources and institutions. Citation analysis could identify the relationships among the most influential publications, and co-authorship analysis revealed the social structure of the research field based on interactions among authors, institutions, and countries. Moreover, co-word analysis revealed the following three clusters: heritage tourism and national identity, ethnic identity, and immigration and cultural identity, which were  categorized according to their themes. ConclusionThe findings showed that the last decade has witnessed an increase in the research on heritage tourism among diaspora and immigrants. Additionally, the representation of outbound tourists’ national–ethnic identity and the representation of destinations’ national–ethnic identity through tourism were among the most popular research topics worthy of further consideration in future studies.